Pengaruh Metode Pemasaran Hard Selling dan Soft Selling di Aplikasi Tiktok terhadap Minat Beli Produk Skincare pada Pengguna Tiktok (Studi Kasus Kecamatan Medan Sunggal) - Simamora, Ivan Hamonangan; Suryani, Wan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Hard Selling and Soft Selling marketing methods on the purchase intention of skincare products among TikTok users in Medan Sunggal District. The research employed a quantitative approach with multiple linear regression analysis. The independent variables were Hard Selling (X1) and Soft Selling (X2), while the dependent variable was purchase intention (Y). Data were collected using a Likert-scale questionnaire distributed to respondents who met the criteria, and then analyzed through validity and reliability tests, t-tests, F-tests, and the coefficient of determination (Adjusted R²). The results indicate that both Hard Selling and Soft Selling have a positive and significant effect on purchase intention when tested individually. Simultaneously, these two strategies also significantly affect purchase intention, with an Adjusted R² value of 0.594, meaning that 59.4% of the variation in purchase intention can be explained by the two marketing methods, while the rest is influenced by other factors outside this study. Further analysis reveals that Soft Selling has a stronger influence compared to Hard Selling in driving consumer purchase intention. This strategy is more effective as it builds trust, provides education, and aligns with TikTok users’ preference for light, personal, and non-coercive approaches. Therefore, skincare businesses are recommended to prioritize Soft Selling strategies in promoting their products on TikTok.